2023
DOI: 10.2147/prbm.s420662
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Performance of Rural Mental Healthcare Services in Saudi Arabia

Eman A Alblowi,
Mona A Shujaa,
Wadi B Alonazi

Abstract: Introduction Recently, the Saudi government has proposed several initiatives to promote mental health, including the national program named Wazen . The objective of this study was to observe the performance of mental hospitals using a balanced scorecard through this federal program. Methods Secondary quantitative analysis was implemented utilizing the Wazen report program data in 2022. The report adopted a balanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Further, it has been shown that occupational stress is often associated with emotional exhaustion, which can lead to the loss of enthusiasm for work, feeling helpless, trapped, and defeated. 2 Frequently reported occupational stressors among healthcare professionals, especially in nursing services are those intrinsic to the job, those related to patient demands, feeling overburdened, related to roles within the organization, and those related to relationships at work and career development. 3 Existing literature on the psychological problems faced by medical practitioners is limited to few nationwide surveys and some specific hospital surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown that occupational stress is often associated with emotional exhaustion, which can lead to the loss of enthusiasm for work, feeling helpless, trapped, and defeated. 2 Frequently reported occupational stressors among healthcare professionals, especially in nursing services are those intrinsic to the job, those related to patient demands, feeling overburdened, related to roles within the organization, and those related to relationships at work and career development. 3 Existing literature on the psychological problems faced by medical practitioners is limited to few nationwide surveys and some specific hospital surveys.…”
Section: Introductionmentioning
confidence: 99%